Cytotoxic Effect of Datura stramonium Extract on Cancer Cell lines: Ala’a H. Merza, Khalil Z. Al- Jeboori, Nahi Y Yaseen - Merza, Ala’a H. (The Iraqi Journal of Veterinary Medicine, 2010)
In order to investigate the in vitro antitumor activity of Datura stramonium seeds on cancer cell lines. Extract of this plant was prepared by using different concentrations of seed extract 3, 3.25, 3.5, 3.75, 4, 4.25, 4.5, 4.75 and 5 mg/ ml. Cytotoxicity was estimated on mammary adenocarcinoma (AMN3), brain cancer, and normal rat embryonic fibroblast (Ref3) cell lines. The results exhibited that the extract has cytotoxic effect by decreasing the viability of AMN3 (42.91%) and brain cell lines (32.79%). However, it produced little effect on viability of normal cell line Ref3, indicating the specificity of this extract against malignant cells